PERBANDINGAN UJI DESALINASI AIR PAYAU DALAM BENTUK SEDIAAN SERBUK, GRANUL, DAN HIDROGEL ALGA HIJAU - Sudrajat Sugiharta; Arum Hasanah; Iin Lidia Putama Mursal; Farhamzah Farhamzah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
This research was motivated by the problem of lack of clean water around the coast of Rainbow Beach in Karawang because the water quality is poor and still brackish. Untreated brackish water poses a risk to human health if drunk for a long time and can trigger skin diseases if used for bathing. The well water taken is located in the Pelangi Coastal Area, Pedes Karawang. This research aims to test the ability of brackish water desalination using powder, granules, and three variations of green algae hydrogel. This research uses a quasi-experimental method by comparing it with zeolite as a standard for brackish water desalination. The research results show that the resulting hydrogel preparation has a solid, brittle shape, a dark green color, and a distinctive odor of green algae. The best viscosity value is in the H4 formula. All green algae hydrogel formulas have good pH values, while the best swelling ratio value is in the H2 formula, and the best gel fraction value is in the H4 formula. From the results of the research that has been carried out, it can be concluded that the hydrogel, granule, and green algae powder preparations can desalinate brackish water based on the results of pH, temperature, salinity, sodium ion, and magnesium ion tests compared with zeolite, where the 6 g hydrogel preparation shows the best desalination capability of brackish water at the three well sample points